Display backlighting systems and methods for adaptive pulse width modulation and modulo pulse width modulation - VEHBI CALAYIR; JAMES E. BROWN; BRET ROTHENBERG; VENKATARAMAN V. IYER (2020)
The present invention relates to a display backlighting systems and methods for adaptive pulse width modulation and modulo pulse width modulation. Aspects of the subject technology relate to an electronic device with a display. The display includes an array of light-emitting diodes. The array includes a plurality of subarrays of the light-emitting diodes. At least one driver circuit is coupled tothe array of light-emitting diodes. The at least one driver circuit is configured to generate an adaptive pulse-width modulated (PWM) signal to control at least one subarray of the plurality of subarrays of the light-emitting diodes. The adaptive PWM signal is designed with each pulse of a group having a pulse width W, each pulse width being reduced until reaching a threshold pulse width, and onepulse being removed from the group of pulses. 本公开涉及显示器背光自适应脉冲宽度调制和模脉冲宽度调制。本主题技术的各方面涉及一种具有显示器的电子设备。显示器包括发光二极管阵列。阵列包括发光二极管的多个子阵列。至少一个驱动器电路耦接到发光二极管阵列。至少一个驱动器电路被配置为生成自适应脉冲宽度调制(PWM)信号以控制发光二极管的多个子阵列中的至少一个子阵列。自适应PWM信号被设计成一组中的每个脉冲具有脉冲